Fostering Self‐Control Development With a Designed Intervention in Physical Education: A Two‐Year Class‐Randomized Trial. Issue 3 (25th August 2020) - Pesce, Caterina; Lakes, Kimberley D.; Stodden, David F.; Marchetti, Rosalba
Abstract : This study evaluated whether a theory‐based intervention in physical education (PE) designed to train self‐control may positively impact children's quick‐temperedness and disruptiveness and whether changes in executive functions (EFs) may be a correlate or antecedent of such effects. One hundred and sixteen children aged 8–9 years participated in a 2‐year intervention and completed three assessments at baseline, 6‐ and 18‐month follow‐ups in quick‐temperedness and disruptiveness, hot and cool EFs. After the intervention, children in the intervention group showed lower quick‐temperedness and disruptiveness and improvement in hot EF. Changes over the intervention period were moderately associated and showed marginal evidence of causal ordering, suggesting that designed PE may benefit self‐control through a possible linkage to hot EF improvement.